Análise metalográfica da estrutura interna de mini-implantes ortodônticos - Vásquez Peralta, Rubén Patricio (2009)
A thorough anchorage in Orthodontics may be obtained through mini-implants, that is, with screws between 1 and 1.8mm in diameter and from 6 to 12mm in length, which are inserted into the maxillary bones. The mini-implants are manufactured with Titanium grade V, an alloy made up of Ti-6Al-4V. The objective of this project was that of analyzing, by means of optic microscopy, the internal structure of orthodontic mini-implants. Subsequently, 6 samples of mini-implants, brand DEWIMED, manufactured in Germany, and 6 more samples, brands SIN and CONEXÃO, manufactured in Brazil, were obtained. The samples were cold embedded in metal metacrilate polymer, longitudinally sectioned (3 samples from every brand) and cross sectioned (the other 3 screws) and successively sanded down with decreasing abrasive grains. After the polishing, a chemical attack was performed, for the contrast of the microstructure of the screw. Once those stages were finished, the sample was observed under an optic microscope with a zoom of up to 2000X, with the objective of detecting the composition of the metal structure, thus verifying possible discontinuities from the surface to the core of the screw. The results showed that the mini-implants which were analyzed did not present any sort of defect on its interior, such as fractures, discontinuities or bubbles, neither on the longitudinal nor on the cross sections. Moreover, it was evident that, on the cross section, all samples assessed presented an Alpha+Beta globular phase, thus fulfilling the requirements of international standards.